Efektivitas Model Pembelajaran Campuran Auditory, Intellectually, Repetition, dan Group Investigation dengan Model Pembelajaran Problem Based Learning terhadap Kreativitas Berpikir - Nugraheny, Hesty; Edie, Sukiswo Supeni; Sutikno, Sutikno (UPEJ Unnes Physics Education Journal, 2019)
The importance of developing students' thinking skills is contained in Permendiknas Number 22 of 2006 concerning standard content. It states that science and technology subjects have the aim of obtaining the basic competencies in science and technology and cultivating critical, creative, and independent thinking. This study intended to determine the effectiveness of the Auditory Intellectually Repetition (AIR) combined with the Group Investigation model and Problem Based Learning model on students' creative thinking skills. This research was conducted in SMP Negeri 1 Kemranjen. The researcher used a quasi-experimental design with an equivalent control group design. The sample in this study was taken by random sampling technique, obtained research samples namely class VIII F as the experimental class and class VIII D as the control class. The method of data collection consisted of documentation and tests. The results of data analysis showed that the mixed learning model of Auditory, Intellectually, Repetition with Group Investigation was effective in improving students' creative thinking. The Problem Based Learning model was also effective in improving students' creative thinking skill with a gain of 0.52 from a maximum score of 1. It was included in the medium criteria. In conclusion, the mixed of Auditory, Intellectually, Repetition and Group Investigation learning model was more effective than Problem Based Learning model in developing students' creative thinking.